Coronenohelicenes with Dynamic Chirality - Weiß, Corinna; Sharapa, Dmitry I.; Hirsch, Andreas (Chemistry - A European Journal, 2020)
The synthesis of a new type of chiral and dynamic nonplanar aromatics containing a combination of fused perylene-based coronenes and helicenes is reported. Either one or two helicene moieties were fused to the bay regions of an extended perylene core. The target compounds contain either identical or two different helicene building blocks. The combination with two helicene units leads to six different isomers, including two pairs of enantiomers and two meso forms. The experimental determination of the isomerization barriers the corresponding double [5]-helicenes revealed activation energies of Ea=24.81 and 25.38 kcal mol−1, which is slightly above the barrier of the parent [5]-helicene. Resolution of all possible regio- and stereoisomers allowed for the systematic investigation of the chiroptical properties. They revealed remarkable dissymmetry factors IgabsI of up to 1.2×10−2, which mirror the synergy between the strong absorbing perylenes and the inherent chirality of helicenes.
CRIS-Team Scopus Importer:2020-10-02
Keywords: dynamic; helicene; isomerization; isomers; perylene

Highly Selective Non-Covalent On-Chip Functionalization of Layered Materials - Tilmann, Rita; Weiß, Corinna; Cullen, Conor P.; Peters, Lisanne; Hartwig, Oliver; Hoeltgen, Laura; Stimpel-Lindner, Tanja; Knirsch, Kathrin; Mcevoy, Niall; Hirsch, Andreas; Duesberg, Georg S. (Advanced Electronic Materials, 2021)
Non-covalent functionalization of layered 2D materials is an essential tool to modify and fully harness their optical, electrical, and chemical properties. Herein, a facile method enabling the selective formation of self-assembled monolayers (SAMs) of perylene bisimide (PBI) on transition metal dichalcogenides (TMDs), directly on the growth substrate (on-chip), is presented. Laterally-resolved infrared atomic force microscopy (AFM-IR) and time-of-flight secondary ion mass spectrometry (TOF-SIMS) are applied as superior techniques to gain detailed information beyond traditional surface analysis techniques, such as Raman spectroscopy and AFM, on TMD/PBI structures. The highly selective functionalization conducted in organic solution on MoS2 and WSe2 opens up a pathway to controllable, versatile functionalization of layered materials, which is highly sought after for its potential in passivation, tuning of properties and applications in optics, electronics, and (bio-) sensing.
CRIS-Team Scopus Importer:2021-01-29
Keywords: 2D materials; perylene bisimides; self-assembled monolayers; surface functionalization; transition metal dichalcogenides

Synthesis and crystal packing of perylene-derivatives with extreme sterically demanding pentaphenylbenzene bay-substituents - Dusold, Carolin; Weiß, Corinna; Hampel, Frank; Hirsch, Andreas (Chemical Communications, 2021)
An unprecedented library of single and double bay-substituted perylene-pentaphenylbenzenes (PPBs) is presented. An extreme core-distortion as well as successful elimination of aggregation interactions of perylenes was confirmed by X-ray analysis. The isomerically pure perylene-PPB hybrids show remarkable differences in their photophysical properties with respect to their regiochemistry as well as different peri-functionalization. This journal is
CRIS-Team Scopus Importer:2021-02-05